The Impacts of Medical Artificial Intelligence to Doctor's Professional Autonomy: Challenges and Countermeasures - Yuqi KANG; Xiaosong HE (Yixue yu zhexue)
In the new medical model of "machine-doctor-patient" constructed by the medical artificial intelligence (AI) prediction models, the "independent judgment" and "independent learning" of some doctors will be affected, that is, the authority in medical diagnosis, treatment decision-making, and independent learning will be dissolved, and may even affect the autonomy of patients. This paper proposes three improvement pathways: human-machine cooperation reconstruction, human-machine relationship reconstruction, and embedded shared decision-making in clinical practice. These approaches aim to enhance physicians' professional autonomy and promote a constructive human-AI collaborative relationship. The goal is to both safeguard physicians' professional value and improve the intelligence and humanization of healthcare services, ultimately advancing smart healthcare toward a higher level of collaborative governance.